Proton imaging of high-energy-density laboratory plasmas - Schaeffer, DB; Bott, AFA; Borghesi, M; Flippo, KA; Fox, W; Fuchs, J; Li, C; Séguin, FH; Park, H-S; Tzeferacos, P; Willingale, L (American Physical Society, 2023)
Proton imaging has become a key diagnostic for measuring electromagnetic fields in high-energy-density (HED) laboratory plasmas. Compared to other techniques for diagnosing fields, proton imaging is a measurement that can simultaneously offer high spatial and temporal resolution and the ability to distinguish between electric and magnetic fields without the protons perturbing the plasma of interest. Consequently, proton imaging has been used in a wide range of HED experiments, from inertial-confinement fusion to laboratory astrophysics. An overview is provided on the state of the art of proton imaging, including a discussion of experimental considerations like proton sources and detectors, the theory of proton-imaging analysis, and a survey of experimental results demonstrating the breadth of applications. Topics at the frontiers of proton-imaging development are also described, along with an outlook on the future of the field.